Understanding the effects of aerodynamic and hydrodynamic shear forces on Pseudomonas aeruginosa biofilm growth. Issue 6 (21st March 2022) - Zhang, Ye; Silva, Dina M.; Young, Paul; Traini, Daniela; Li, Ming; Ong, Hui Xin; Cheng, Shaokoon
Abstract: Biofilms are communities of bacterial cells encased in a self‐produced polymeric matrix and exhibit high tolerance towards environmental stress. Despite the plethora of research on biofilms, most biofilm models are produced using mono‐interface culture in static flow conditions, and knowledge of the effects of interfaces and mechanical forces on biofilm development remains fragmentary. This study elucidated the effects of air–liquid (ALI) or liquid–liquid (LLI) interfaces and mechanical shear forces induced by airflow and hydrodynamic flow on biofilm growing using a custom‐designed dual‐channel microfluidic platform. Results from this study showed that comparing biofilms developed under continuous nutrient supply and shear stresses free condition to those developed with limited nutrient supply, ALI biofilms were four times thicker, 60% less permeable, and 100 times more resistant to antibiotics, while LLI biofilms were two times thicker, 20% less permeable, and 100 times more resistant to antibiotics. Subjecting the biofilms to mechanical shear stresses affected the biofilm structure across the biofilm thickness significantly, resulting in generally thinner and denser biofilm compared to their controlled biofilm cultured in the absence of shear stresses, and the ALI and LLI biofilm's morphology was vastly different. Biofilms developed under hydrodynamic shear stress also showed increased antibiotic resistance. These findings highlight the importance of investigating biofilm growth and its mechanisms in realistic environmental conditions and demonstrate a feasible approach to undertake this study using a novel platform. Abstract : The abstract figure shows the effects of mechanical shear stress on biofilm development. Biofilm was cultured on different interfaces and flow conditions associated with different mechanical shear stress are created in a microfluidic device. Results show that mechanical shear stress affects biofilms' growth, morphology, permeability, and antibiotic susceptibility.